Effects of urbanization on avian diversity and human-nature interactions in tropical environments - Awoyemi, A.G. (University of Granada, 2025)
Urbanization is a rapidly expanding global phenomenon that poses significant threats to biodiversity. Despite its importance, the impacts of urbanization on biodiversity in certain regions remain understudied. Recent studies have highlighted the need for more research on the topic, particularly in Africa, where unprecedented urbanization overlaps with vast biodiversity. Thus, this thesis investigated the impacts of urbanization on socioecological systems in the Afrotropics, providing data useful in achieving sustainable urban development in line with SDG Goal 11 (Sustainable Cities and Communities) in the region. This thesis began with a comprehensive systematic literature review to assess the current state of urban ecology in Africa (Chapter 1). The review revealed a striking knowledge gap, with only 795 relevant papers published in the last century (1920—2020), much less than those from other continents. Notably, a disproportionate number of these studies (40%) were conducted in South Africa, indicating a significant geographical bias in our current knowledge on the topic. This review found that research efforts are driven by economic wealth (GDP) and the importance of conservation in African urban ecology. However, the review also exposed a surprising oversight: the Afrotropics, which is the most urbanized and biodiverse-rich African region, is not a primary focus of study. Furthermore, most urban ecology studies in Africa were conducted in a single city (55%), with substantial knowledge gaps persisting across taxonomic groups, scientific fields, and ecoregions. To partially address these important gaps, this thesis focused on investigating different research questions in multiple cities in Nigeria (Chapters 2—5), a typical Afrotropical country experiencing rapid urbanization. These additional chapters investigated the impacts of urbanization on bird taxonomic, functional and phylogenetic diversity (Chapters 2—3), avian-mediated regulating ecosystem services, including pest control, seed dispersal, pollination, and scavenging (Chapter 4), and human-nature interactions (Chapter 5). The results of these studies unequivocally demonstrated that urbanization has profound negative impacts on bird diversity and ecosystem services in the Afrotropics. Compared to non-urban areas, urban areas exhibited significantly lower bird taxonomic diversity (Chapter 2) and reduced provisioning of essential ecosystem services provided by wildlife, including pest control, seed dispersal and pollination (Chapter 4). Scavenging was the only bird-mediated ecosystem service enhanced by urban development (wet season). Furthermore, certain urban attributes, such as the presence of vehicles and pedestrians, were found to compromise bird phylogenetic divergence and ecosystem service provision, particularly pollination and seed dispersal. However, the results also highlight the potential for targeted conservation efforts to mitigate these negative impacts. Notably, the presence of water bodies and specific vegetation types, such as canopy and bush cover, can significantly enhance multiple components of bird diversity and crucial bird-mediated regulating ecosystem services (Chapters 2 and 4). By preserving and restoring these key habitat features, it may be possible to reverse the decline of bird diversity and the associated regulating ecosystem services in Afrotropical cities, particularly seed dispersal and pollination. Chapter 3 presents a novel application of machine learning and remote sensing techniques in estimating local habitat variables influencing bird diversity components across urban and non-urban areas. This study revealed that the Modified Chlorophyll Absorption Ratio Index (MCARI) is the most effective indicator of taxonomic and phylogenetic bird diversity in the Afrotropics. In contrast, the Normalized Difference Water Index 2 (NDWI2) and Soil Adjusted Total Vegetation Index (SATVI) were found to be the best predictors of functional diversity and phylogenetic divergence, respectively. Interestingly, the Normalized Difference Vegetation Index (NDVI), a commonly used predictor across regions and topics, ranked relatively low (25th percentile) in most cases. These results recommended the use of these alternative predictors (MCARI, NDWI2 and SATVI) rather than the NDVI in predicting bird biodiversity in urban and non-urban areas of the Afrotropics. This is likely due to NDVI's limitations, including scaling issues, saturation in high-biomass areas, and sensitivity to soil brightness, which can compromise its accuracy in diverse Afrotropical environments. The remote sensing approach employed in this study offers a potentially more efficient and cost-effective method for estimating local habitat variables compared to traditional manual estimation techniques. By leveraging machine learning algorithms and remotely sensed data, this approach can help reduce the labor, expense, and investigator error associated with manual data collection. In addition to the ecological impacts, urbanization also has significant social implications. By investigating the extinction of experience concept among urban dwellers in Nigeria, Chapter 5 found that most citizens had little or no contact with nature. The main reasons cited for this disconnection were lack of time, money, and nearby natural areas. The study also found that respondents with higher nature contact were more connected to nature, and that the perception of neighborhood safety was an important factor promoting nature contact. Furthermore, the study also found that respondents living in Lagos, and those with lower levels of income and education, showed greater dissociation from nature. These findings could be useful to fight against the worrying extinction of experience in the region, providing potential factors to consider and implement in future urban development plans in the Afrotropics. Overall, the Chapters of this thesis highlight the need for more research on the impacts of urbanization on biodiversity and ecosystem services in the Afrotropics. They also emphasize the importance of promoting nature contact and experience among urban dwellers, particularly in regions with rapid urbanization such as the study area (i.e. Nigeria). By addressing these knowledge gaps and promoting nature experience, we can work towards creating more sustainable and resilient urban ecosystems that will benefit both people and the environment.